Efeito da densidade de plantio de pequenos bulbilhos e do tipo de cobertura sobre o rendimento de alho-planta, em três cultivares de alho (Allium sativum L.) - Alves de Menezes Sobrinho, João; A A Couto, Flávio; Virgílio Lobo Medina, Paulo; Mário Regina, Sérgio (Revista Ceres, 2025)
The objective of this study was to verify the effect of 3 planting densities of "palito" (mature garlic cloves not fully developed in size) under 3 types of dry mulch cloves on the production of "alho-planta". Cultivars employed were 'Branco', 'Roxo' and 'Barbado'.